Dimensional properties of the cobs for machine design - Romantchik Kriuchkova, Eugenio; Bernabe López, Erubiel; Cruz Meza, Pedro; Cebada Reyes, José Guillermo; Velázquez López, Noé (Revista Mexicana de Ciencias Agrícolas, 2019)
In order to design cutting machines and deburders of cobs (Zea mays L.), it is necessary to know the geometric properties of the fruit that form the input data for the evaluation of the mathematical models of the fruit-machine system. Three new geometric characteristics were determined: optimal cutting diameter (c), base length to the largest diameter (lbdm) and base length to the optimum cutting diameter (lbco) of a sample of 50 cobs of white corn of the variety Murano, from the state of Morelos, as well as total length (lt) and greater diameter (dm). Similarly, for a sample of 103 Arroz variety cobs of the state of Veracruz, lbco, lbdm, dm and lt were determined, a photographic record was also made and processed with OpenCV software with determination of two parameters plus-area (A) and length from base to centroid (lbc). Statistical analysis showed that there is a simple correlation of 0.905 between lbco-lbdm and two multiple correlation coefficients of 0.904 between dm-lbdm-lbco, and 0.917 between lt-lbdm-lbco for the Murano variety. The Arroz variety showed a multiple correlation of 0.66 between lbco-dm-lbdm-lt-A-lbc. With the results, different mathematical models of relationship between the parameters of the cob were established for its application in the design of an improved prototype of defoliator.